# 3 ∫ 2 E − X D X - Mathematics

Sum

$\int\limits_2^3 e^{- x} dx$

#### Solution

$\text{Here }a = 2, b = 3, f\left( x \right) = e^{- x} , h = \frac{3 - 2}{n} = \frac{1}{n}$

Therefore,

$\int_2^3 e^{- x} d x = \lim_{h \to 0} h\left[ f\left( a \right) + f\left( a + h \right) + f\left( a + 2h \right) + . . . . . . . . . . . . + f\left( a + \left( n - 1 \right)h \right) \right]$

$= \lim_{h \to 0} h\left[ f\left( 2 \right) + f\left( 2 + h \right) + . . . . . . . . . . + f\left( 2 + \left( n - 1 \right)h \right) \right]$

$= \lim_{h \to 0} h\left[ e^{- 2} + e^{- \left( 2 + h \right)} + e^{- \left( 2 + 2h \right)} + . . . . . . . + e^{- \left( 2 + \left( n - 1 \right)h \right)} \right]$

$= \lim_{h \to 0} h e^{- 2} \left[ \frac{\left( e^{- h} \right)^n - 1}{e^{- h} - 1} \right]$

$= \lim_{h \to 0} e^{- 2} \left[ \frac{e^{- 1} - 1}{\frac{e^{- h} - 1}{- h}} \right] \times - 1 ....................\left(\text{Since nh = 1 }\right)$

$= \left( e^{- 2} - e^{- 3} \right)$

Concept: Definite Integrals Problems
Is there an error in this question or solution?

#### APPEARS IN

RD Sharma Class 12 Maths
Chapter 20 Definite Integrals
Revision Exercise | Q 65 | Page 123
Share